2020
DOI: 10.1155/2020/7380172
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthetic-Induced Neurotoxicity in the Immature Brain: Reevaluating the Confounding Factors in the Preclinical Studies

Abstract: General anesthetic (GA) is used clinically to millions of young children each year to facilitate surgical procedures, relieve perioperative stress, and provide analgesia and amnesia. During recent years, there is a growing concern regarding a causal association between early life GA exposure and subsequently long-term neurocognitive abnormalities. To address the increasing concern, mounting preclinical studies and clinical trials have been undergoing. Until now, nearly all of the preclinical findings show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that 1.5 MAC sevoflurane inhalation for 2 h potentiated surgery impaired cognitive function [ 27 ]. Prolonged (6–9 h) exposure to high concentrations (3–4%) of sevoflurane causes neuroinflammation and neuronal apoptosis and leads to long-term cognitive impairment [ 28 ]. Exposure to sevoflurane increased iron content in hippocampal neurons compared with cells not exposed to sevoflurane [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 1.5 MAC sevoflurane inhalation for 2 h potentiated surgery impaired cognitive function [ 27 ]. Prolonged (6–9 h) exposure to high concentrations (3–4%) of sevoflurane causes neuroinflammation and neuronal apoptosis and leads to long-term cognitive impairment [ 28 ]. Exposure to sevoflurane increased iron content in hippocampal neurons compared with cells not exposed to sevoflurane [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Designing protective measures or alternative anesthetics require the understanding of the mechanisms that mediate GA neurotoxic effects. Although various studies aiming to delineate pathways that mediate these processes were reported in the last several years, most of them were performed in rodents ( Jevtovic-Todorovic, 2016 ; Lin et al, 2017 ; Luo et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%